(untitled) (Research, Society and Development, 2022)
The insertion of applied biotechnology in the cosmetology industry has generated a great impact in several aspects, allowing cosmetic companies to discover, develop and produce components of cosmetic formulations and evaluating their activity on the skin, being an alternative tool for the development of actives with cell renewal action, preventive and in the fight against aging, in the treatment of disorders related to the facial skin. It aims to emphasize the need for facial self-care and to show the benefits of fermented dermocosmetics in the treatment of the skin due to the prolonged use of a protective mask. An online data survey was carried out from June to November 2022. Through the search on reliable scientific research platforms such as Google Scholar, Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL), government websites, from the descriptors "biotechnology, cosmetics, hydroxy acids, skin diseases; skin care”. Prolonged use of the mask caused moisture, steam, dirt, sweat, saliva or mucus to be trapped between the mask and the skin causing irritation and sensitivity of the site, in addition to the friction of the mask on the face, thus being one of the factors that caused skin barrier damage and facial sensitization. It should be noted that using acids incorrectly could trigger other skin disorders, so it is always recommended to consult a health professional, such as a dermatologist, before applying the products. It is also worth mentioning that just the use of fermented dermocosmetics is not enough for healthy skin, but a set of actions to balance the body.